2022
DOI: 10.3390/agronomy12040838
|View full text |Cite
|
Sign up to set email alerts
|

Can Epigenetics Guide the Production of Better Adapted Cultivars?

Abstract: As the global population continues to grow, food demand will be reaching levels which current agricultural practices cannot meet. This projected demand combined with the negative impacts of climate change on crop production calls for more careful breeding efforts to develop better adapted plants more tolerant to climate fluctuations. Fortunately, the development of molecular biology techniques like genome, transcriptome and epigenome sequencing now offer new approaches to help classical breeding meet these cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…The wild-type scion will be non-transgenic (free of transgene integration into the genome). Tonosaki et al 10.3389/fpls.2022.958350 Frontiers in Plant Science frontiersin.org (Turcotte et al, 2022), and these technologies will also be useful for screening epigenome edited crops.…”
Section: Implementation In Breedingmentioning
confidence: 99%
See 1 more Smart Citation
“…The wild-type scion will be non-transgenic (free of transgene integration into the genome). Tonosaki et al 10.3389/fpls.2022.958350 Frontiers in Plant Science frontiersin.org (Turcotte et al, 2022), and these technologies will also be useful for screening epigenome edited crops.…”
Section: Implementation In Breedingmentioning
confidence: 99%
“…It is clear that taking practical advantage of the potential of epigenetics in crop breeding is in its infancy. While a great deal of interest and enthusiasm has been generated, as evidenced by the numerous review articles addressing the potential of this new science and technology (see for example: Springer and Schmitz, 2017;Kawakatsu and Ecker, 2019;Dalakouras and Vlachostergios, 2021;Turcotte et al, 2022), there are relatively few cases of successful application of this new science to plant breeding, with "successful application" being defined as commercial release of a new cultivar or hybrid. This could be due to the inherent instability and variability of epigenetic programming and the difficulty in identifying precise treatments and approaches for its utilization.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The availability of sufficient variability in the gene pools is pivotal for executing meaningful and successful crop improvement programs to ameliorate various biotic and abiotic stresses arising due to the changing stressful global climates ( Samantara et al, 2021 ; Krishnaswami et al, 2022 ). Stress exposure cascades a response-signaling cycle in plants that along with genetic modifications leads to many epigenetic changes routed through mechanisms such as chromatin remodeling, DNA methylation, histone modification, and non-coding RNAs ( Turcotte et al, 2022 ). These epigenetic mechanisms have resulted in novel epialleles associated with morphological, metabolic, and developmental traits in plants ( Tirnaz and Batley 2019 ) that can be exploited for developing new climate-resilient crop varieties to mitigate the challenges of changing environments ( Springer and Schmitz, 2017 ; Kawakatsu and Ecker, 2019 ; Varotto et al, 2020 ; Kakoulidou et al, 2021 ; Guarino et al, 2022 ) and help in crop domestication by targeting epigenetic diversity to engineer crop plants for optimal crop production ( Ding and Chen, 2018 ).…”
Section: Applications Of Epigenetic Mechanisms In Crop Breeding and D...mentioning
confidence: 99%
“…Similarly, alterations in H3K4me2 in maize helped in mitigating abiotic and biotic stresses ( Samantara et al, 2021 ) and histone acetylation was shown to regulate drought stress in tomato and Arabidopsis ( González et al, 2013 ; Zheng et al, 2016 ). It has been demonstrated that histone deacetylase HDA9 plays a key role in regulating drought stress in plants ( Turcotte et al, 2022 ). Further, miRNAs regulated the expression of the OsSPL14 gene affecting the panicle branching and increasing the rice yield ( Miura et al, 2010 ).…”
Section: Applications Of Epigenetic Mechanisms In Crop Breeding and D...mentioning
confidence: 99%
See 1 more Smart Citation